Total choline quantification measured by 1H MR spectroscopy as early predictor of response after neoadjuvant treatment for locally advanced breast cancer: The impact of immunohistochemical status. Issue 4 (16th April 2018) - Drisis, Stylianos; Flamen, Patrick; Ignatiadis, Michael; Metens, Thierry; Chao, Shih‐Li; Chintinne, Marie; Lemort, Marc
Abstract : Background: Validation of new biomarkers is essential for the early evaluation of neoadjuvant treatments. Purpose: To determine whether measurements of total choline (tCho) by 1H spectroscopy could predict morphological or pathological complete response (pCR) of neoadjuvant treatment and whether breast cancer subgroups are related to prediction accuracy. Study Type: Prospective, nonrandomized, monocentric, diagnostic study. Population: Sixty patients were initially included with 39 women participating in the final cohort. Field Strength/Sequence: A 1.5T scanner was used for acquisition and MRS was performed using the syngo GRACE sequence. Assessment: MRS and MRI examinations were performed at baseline (TP1), 24–72 hours after first chemotherapy (TP2), after the end of anthracycline treatment (TP3), and MRI only after the end of taxane treatment (TP4). Early (EMR) and late (LMR) morphological response were defined as %ΔDmax13 or %ΔDmax14, respectively. Responders were patients with %ΔDmax >30. Pathological complete response (pCR) patients achieved a residual cancer burden score of 0. Statistical Tests: T ‐test, receiver operating characteristic (ROC) curves, multiple regression, logistic regression, one‐way analysis of variance (ANOVA) analysis were used for the analysis. Results: At TP1 there was a significant difference between response groups for tCho1 concerning EMR prediction ( P  = 0.05) and pCR ( P  < 0.05) and for Kep 1 ( P  = 0.03) concerning LMR prediction. At TP2, no modification of tCho and other parameters could predict response. At TP3, ΔtCho, ΔDmax, and ΔVol could predict LMR ( P  < 0.05 for all parameters), pCR ( P  < 0.05 for all parameters), and ΔK trans could predict only pCR ( P  = 0.04). Logistic regression at baseline showed the highest area under the curve (AUC) of 0.9 for prediction of pCR. The triple negative (TN) subgroup showed significantly higher tCho at baseline ( P  = 0.02) and higher ΔtCho levels at TP3 ( P  < 0.05). Data Conclusion: Baseline measurements of tCho in combination with clinicopathological criteria could predict non‐pCR with a high AUC. Furthermore, tCho quantification for prediction of pCR was more sensitive for TN tumors. Level of Evidence: 1 Technical Efficacy: Stage 4 J. Magn. Reson. Imaging 2018;48:982–993.